The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12916-020-1503-6
|View full text |Cite
|
Sign up to set email alerts
|

Remission of autoimmune diabetes by anti-TCR combination therapies with anti-IL-17A or/and anti-IL-6 in the IDDM rat model of type 1 diabetes

Abstract: Background: The cytokine IL-17 is a key player in autoimmune processes, while the cytokine IL-6 is responsible for the chronification of inflammation. However, their roles in type 1 diabetes development are still unknown. Methods: Therefore, therapies for 5 days with anti-IL-17A or anti-IL-6 in combination with a T cell-specific antibody, anti-TCR, or in a triple combination were initiated immediately after disease manifestation to reverse the diabetic metabolic state in the LEW.1AR1-iddm (IDDM) rat, a model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…In addition, the outcomes are in line with Robinson, et al [19] who mentioned that IL-6 is a pleiotropic cytokine that can be found in high levels in the blood and vitreous of DR (diabetic retinopathy) patients. Jorns, et al [20] who reported that during the inflammation process in the T1D pancreas, the pro-inflammatory cytokine IL-6 was expressed in all immune cell subtypes. Tsalamandris, et al [21] indicated that IL-6 plays a role in pathogenesis of diabetic.…”
Section: Animals and Experimental Design: Thirty Malementioning
confidence: 99%
“…In addition, the outcomes are in line with Robinson, et al [19] who mentioned that IL-6 is a pleiotropic cytokine that can be found in high levels in the blood and vitreous of DR (diabetic retinopathy) patients. Jorns, et al [20] who reported that during the inflammation process in the T1D pancreas, the pro-inflammatory cytokine IL-6 was expressed in all immune cell subtypes. Tsalamandris, et al [21] indicated that IL-6 plays a role in pathogenesis of diabetic.…”
Section: Animals and Experimental Design: Thirty Malementioning
confidence: 99%
“…Additional RAGE ligands include the high-mobility group of box protein 1 (HMGB1), S100 proteins, β-amyloid, β-sheet fibrils and lipopolysaccharide [33]. Research findings gained over the last two decades argue for a link of AGEs and RAGE to the T1D pathogenesis, yet a possible role of AGEs in islet function and survival within homeostasis and disease states is still elusive [28].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, RAGE and AGEs are the focus of therapy for diabetes' conditions such as diabetic retinopathy [20], as well as in other inflammatory diseases such as myasthenia gravis [21]. We have shown that the LEW.1AR1-iddm rat model of human T1D [22] is a useful experimental tool to study various aspects, including development, progression and therapy of T1D [23][24][25][26][27][28][29]. In a previous study [29], we investigated possible implications of dimethylation and citrullination of Arg residues in proteins in four organs of LEW.1AR1-iddm rats under different diabetic metabolic conditions compared to normoglycaemic healthy control rats.…”
Section: Introductionmentioning
confidence: 99%
“…20 Our previous research shows that the higher the serum IL-17A level, the higher the incidence and severity of DR. The underlying mechanism can be summarized as: (1) IL-17A can trigger the destruction of the fundus vascular barrier as well as increase the degree of inflammation of 10 Global DR research studies have revealed that a longer T2DM duration, increasing age, higher HbA1c levels, and poorer blood pressure control were strongly correlated with DR. 13,22 In this study, the longer the DM duration, the higher the prevalence and severity of DR, which is consistent with previous studies. 23 Many previous studies have shown that FCP is related to DR. 24 An earlier study showed that after adjustment for confounding factors, C-peptide and insulin levels were significantly correlated with extent of DR in Latinos with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Triple combination therapy effectively induced blood glucose homeostasis involving normalized serum C-peptide concentrations by controlling autoimmunity and improving anti-inflammatory effects. 10 IL-17A may be involved in the pathological process of DR, but the relationship between them is still unclear. As the relationship between IL-17A and DR is complicated, more research is needed.…”
Section: Introductionmentioning
confidence: 99%